Antibacterial activity of chlorhexidine after final irrigation with ethanol: CLSM and culture-based method analysis - Suman, Juliana Martins; Kuga, Milton Carlos [UNESP]; Da Rosa, Ricardo Abreu; Santini, Manuela Favarin; Grazziotin-Soares, Renata; Montagner, Francisco; Reis So, Marcus ViniCius (Wiley-Blackwell, 2015)
This study investigated the effect of 95% ethanol on the antibacterial properties of 2% chlorexidine (CHX) over monospecies biofilm (Enterococcus faecalis) through a culture-based method, and over multispecies biofilm using confocal laser scanning microscopy (CLSM). For monospecies model, E. faecalis biofilm was induced in 40 root canals. The irrigation procedures were: Ssaline solution; S/CHXsaline solution+CHX; Eethanol; and E/CHXethanol+CHX. Microbial sampling was performed at three periods: before (S1), immediately after (S2), and 72 h after the final flush (S3). For multispecies biofilm model, 28 sterilized bovine dentin blocks were fixed on a removable orthodontic device to allow intraoral biofilm development. Seven samples were used in each group. Statistical analysis was carried out by using the Kruskal-Wallis test and Dunn's test for multiple comparisons. There was a significant reduction in CFUs count immediately after the final flush (S2) in all experimental groups (P<0.05). However, only S/CHX, E and E/CHX groups had CFU counts close to zero, without differences among them (P>0.05). After 72h (S3), the S/CHX and E/CHX groups had CFU counts near zero (P>0.05). The CFU count increased in S3 for S and E groups (P<0.05). CLSM showed that the percentages of remaining live cells were similar in S/CHX, E, and E/CHX groups (P>0.05). The S group had the highest percentage of live cells (P<0.05). The 95% ethanol did not interfere in the antibacterial properties of 2% CHX over mono- and multispecies biofilms. Microsc. Res. Tech. 78:682-687, 2015. (c) 2015 Wiley Periodicals, Inc.
Keywords: biofilms; confocal microscopy; root canal irrigants